The metabolic syndrome: prevalence, associated factors, and impact on survival among older persons in rural Bangladesh. - Masuma Akter Khanam (Public Library of Science (PLoS), 2011)
Objectives To describe the prevalence of the metabolic syndrome (MetS) among older persons in rural Bangladesh, to investigate whether the prevalence varies by age, sex, literacy, marital status, nutritional status and socio-economic status, and to assess the impact of MetS on survival. Methods The study consisted of 456 persons who were aged ≥60 years living in a rural area of Bangladesh during July 2003-March 2004. Data were collected through interview, clinical examination, and laboratory tests, and their survival status until 30(th) June 2009 was ascertained through the Matlab surveillance system. We defined MetS following the NCEP ATP III criteria, with minor modifications, i.e., presence of any three of the following: hypertension (BP ≥130/85 mm Hg); random blood glucose (RBG) level ≥7.0 mmol/L; hyper-triglyceridemia (≥2.28 mmol/L); low level of HDL-cholesterol (<1.04 mmol/L for men and <1.29 mmol/L for women); and BMI ≥25.0 kg/m(2). Data were analysed with logistic regressions for the influential factors of MetS, and with Cox models for the association of MetS with the survival status. Findings The overall prevalence of MetS was 19.5%, 20.8% in women, and 18.0% in men. Asset-index and nutritional status were independently associated with MetS. During 4.93 years of follow-up, 18.2% died. In the presence of high RBG, MetS has a significant negative effect on survival (69.4% vs 95.2%, log rank p = 0.02). Conclusion This study highlights the importance of the metabolic syndrome in rural Bangladesh. Our findings suggest that there is a need for screening programmes involving the metabolic syndrome to prevent diabetes and cardiovascular diseases.